Boosted Thermal Storage Performance of LiOH·H2O by Carbon Nanotubes Isolated Multilayered Graphene Oxide Frames - Yuxian Wang; Jing Gu; Xian Li; Yan Zhu; Hongyun Hu; Huan Liu; Guangqian Luo; Hong Yao (Advances in Materials Science and Engineering)
Cellulose-originated three-dimensional graphene oxide CNT-modified LiOH·H2O (3D-GO-CNTs-LiOH·H2O) was synthesized by the hydrothermal method. LiOH·H2O nanoparticles (5–50 nm) were homogeneously dispersed inside the 3D-GO-CNTs frames. The composite showed enhanced heat storage density, excellent thermal conductivity, and greatly improved hydration rate due to both the hydrophilic reaction interface of 3D-GO-CNTs frames and reduced size of LiOH·H2O nanoparticles. LiOH·H2O content ratio of 23% (3D-GO-CNTs-LiOH·H2O-1) results in best heat storage performance with activation energy of 23.8 kJ/mol, thermal conductivity of 3.06 W/m·K, and heat storage capacity of 2800 kJ/kg. 3D-GO-CNTs-LiOH·H2O shows 4.2 folders heat storage capacity than that of pristine LiOH·H2O after the same hydration reaction. Other composite materials also show good performance: 3D-GO-CNTs-LiOH·H2O-2 (activation energy: 28.5 kJ/mol, thermal conductivity: 2.33 W/m·K, and heat storage capacity: 2051 kJ/kg.); 3D-GO-CNTs-LiOH·H2O-3 (activation energy: 32.3 kJ/mol, thermal conductivity: 2.01 W/m·K, and heat storage capacity: 1983 kJ/kg.). The addition of cellulose originated 3D-GO-CNTs was proved to be an excellent strategy to boost the heat storage performance of LiOH·H2O.